2012
DOI: 10.1590/s1980-57642012dn06040003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural abnormalities in the cerebellum and dementia, posttraumatic stress disorder and bipolar disorder

Abstract: New evidence suggests that the cerebellum has structural and functional abnormalities in psychiatric disorders.ObjectiveIn this research, the goal was to measure the volume of the cerebellum and its subregions in individuals with psychiatric disorders and to relate these findings to their symptoms.MethodsPatients with different degrees of cognitive impairment (Epidemiology of the Elderly - UNIFESP) and patients with post-traumatic stress disorder (PTSD) from population studies were analyzed. Also, patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Recent work by Holmes and colleagues also found reduced nodal strength in the cerebellum of PTSD patients, as well as reduced volume and structural covariance (45). Other studies have also reported structural and functional abnormalities in the cerebellum in PTSD (46)(47)(48)(49)(50)(51). Importantly, the cerebellar abnormalities in the current study were evident only during symptom provocation.…”
Section: Figure 4 Effect Of Symptom Provocation On Salience Global Csupporting
confidence: 64%
“…Recent work by Holmes and colleagues also found reduced nodal strength in the cerebellum of PTSD patients, as well as reduced volume and structural covariance (45). Other studies have also reported structural and functional abnormalities in the cerebellum in PTSD (46)(47)(48)(49)(50)(51). Importantly, the cerebellar abnormalities in the current study were evident only during symptom provocation.…”
Section: Figure 4 Effect Of Symptom Provocation On Salience Global Csupporting
confidence: 64%
“…For example, cerebellar volume has been shown to be lower in adolescents 35 and adults with PTSD, 36,37 with cerebellum volume negatively correlating with PTSD symptoms. Furthermore, meta-analyses of both resting-state 38 and task-based 39 neuroimaging studies indicate hypoactive cerebellar function in PTSD. A recent study found alterations in functional connectivity from distinct cerebellar seeds to brain regions involved in emotional regulation, somatosensory processing and memory retrieval in PTSD, with distinct patterns of cerebellar alterations in the dissociative subtype of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, accumulating evidence repeatedly demonstrates functional and structural abnormalities in the cerebellum of PTSD patients (34)(35)(36)(37)(38)(39). Moreover, two recent studies have shown reduced functional nodal strength in the cerebellum in PTSD (19,40).…”
Section: Figure 3 the Effects Of Psychotherapy On Executive Connectimentioning
confidence: 96%